Knowledge Economy: Creation Perspectives Under the Conditions of EU Enlargement - Melnikas, Borisas (Ekonomika, 2005)
The problems and possibilities of the creation of the knowledge based society and knowledge economy in the European Union are described and analysed.Possibilities for the development of new forms of economic, social and technological headway designed to create and further improve economies based on knowledge are analyzed here.The main emphasis is put on national and regional economic specialization and creation of new networks of clusters in the situation of the development of the European Union. We have found that c/usterization oriented towards the increase of efficiency of various national and regional economics is a critical precondition for sl.lccess/ul creation of modem economy based on knowledge, both in the whole space of the European Union and particular countries.Another idea - a concept of creation of regional and cross-regional clusters and their networks also known as “economic oazes” - is suggested here. It i explained in the paper that in the economies based on knowledge development of clusters and their networks will soon become one of the core forms of economic and technological advancement.Further on, the variety of clusters and their networks is defined, and the idea of clusterization generally oriented towards creation and promotion of high technologies is given.In addition, some typical factors of the economic and social development of the European Union are being described here, and it is subsequently proved that these factors reflect on the common context of creation of the knowledge based economies. Understanding of these actors allows us to consequently implement strategies of two types that could create the economics based on knowledge: firs these are the strategies oriented towards integration of the processes of economic and social development along with the strategies oriented towards the syntesis of the remits of the economic endeavours and technology advancement of different origins.The need for imp/ementtUion of these strategies of two types mean that new types of management will have to be developed in the situation of knowledge based economies: these patterns will be built on the Weas of integration (the patterns of this kind are designed to create new formations), along with the patterns based on the ideas of synthesis (the patterns are designed to create quantitatively new quality systems).The use of the both patterns in the future will be critical within both the processes of clusterization and creation of other economies based on knowledge.The promotion of the patterns based on the ideas of integration and synthesis is a core prerequisite for encouragement of innovations and improvement of technology transmit ion systems. Further research dedicated to the patterns mentioned above, is a promising trend of the science of management and administration directly connected to the need for creation of knowledge based economies.